Participants of the Accounting Communication Process - Masztalerz, Marek (Studia Oeconomica Posnaniensia, 2019)
The main purpose of the article is organize the nomenclature regarding the participants of the communication process in accounting in its policy and practice, including six categories of participants, such as the creator, source, addresser (sender), recipient, addressee and user of information. The article is conceptual and the descriptive analysis is the main research method. The article explains the semantic differences between the participants of accounting communication and it is indicated in relation to who or what should be used. It is also showed that there is not always a semantic agreement between the creator, the sender and the source of the message, and between the addressee, the recipient and the user of the information. The contribution of the article is on the one hand an ordering of the nomenclature used by accounting science in describing communication processes, and on the other - on the identification of non-obvious participants in these processes.